2020
DOI: 10.3390/agronomy10070982
|View full text |Cite
|
Sign up to set email alerts
|

Soil Arthropod Responses in Agroecosystem: Implications of Different Management and Cropping Systems

Abstract: The EU’s Common Agricultural Policy (CAP 2014–2020) on soil management points to the combination of sustainable food production with environmental protection, reduction of CO2 emissions, and safeguarding of soil biodiversity. In this study, three farms (in the Emilia-Romagna region), managed with both conventional and conservation practices (the last ones with and without sub-irrigation systems), were monitored from 2014 to 2017 to highlight the impact of different crops and soil managements on soil ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 53 publications
2
19
1
Order By: Relevance
“…We also found that crop type may have a role in determining soil biology health, as already observed in other agricultural contexts [79]. However, because of unbalanced sampling, we cannot disentangle the possible effect of crop type from those of management and land protection, and further research is needed to explore the role of crop type.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We also found that crop type may have a role in determining soil biology health, as already observed in other agricultural contexts [79]. However, because of unbalanced sampling, we cannot disentangle the possible effect of crop type from those of management and land protection, and further research is needed to explore the role of crop type.…”
Section: Discussionsupporting
confidence: 68%
“…Arthropods are the most abundant and diversified group among soil faunas [53], and in agro-ecosystems they provide essential ecological services, including the decomposition of crop residues to form humus and the recycling of mineral nutrients for successive crops [54][55][56]. Owing to their ability to respond to variations in environmental conditions, soil properties, and changes in land management, soil arthropods are gaining increasing interest as effective indicators of soil biology quality [27,31,40,[57][58][59][60], especially in agroecosystems or polluted or degraded sites [6,38,48,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, QBS under S was significantly higher (+48%) than in the treatments receiving tillage, while BCM did not show any significant differences. Tillage is known to be a practice that hampers microarthropod communities by modifying chemical and physical soil properties, thereby negatively impacting QBS values [93,95]. Indeed, higher QBS scores were reported on arable lands when no-till + crop residue retention was compared with conventional tillage [96,97].…”
Section: Effects Of Soil Management On a Soil's Biological Healthmentioning
confidence: 99%
“…Several approaches and multivariate methods have been recently developed to detect the changes in the microarthropod community structure and to exploit its actual bioindication power [21]. Soil biodiversity loss, i.e., the reduction of living forms (in terms of both quantity and variety) and their related roles, cause a deterioration of the soil functions or ecosystems [22][23][24][25]. The soil status can be assessed by the functional biodiversity; by this, microarthropods can be characterized based on diverse feeding strategies and different adaptation degrees allowing them to inhabit soil microhabitats [26].…”
Section: Introductionmentioning
confidence: 99%